2006
DOI: 10.1353/foc.2006.0015
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Higher Education in Social Mobility

Abstract: Most Americans expect the nation's colleges and universities to promote the goal of social mobility to make it possible for anyone with ability and motivation to succeed. But according to Robert Haveman and Timothy Smeeding, income-related gaps both in access to and in success in higher education are large and growing. In the top-tier colleges and universities, almost three-quarters of the entering class is from the highest socioeconomic quartile. The pool of qualified youth is far greater than the number admi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
180
0
5

Year Published

2009
2009
2019
2019

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 285 publications
(186 citation statements)
references
References 26 publications
1
180
0
5
Order By: Relevance
“…Gaps in college degree attainment by socioeconomic status are even more pronounced. Among the high school graduating class of 1992, only 7 percent of students from families in the lowest socioeconomic quartile completed a four-year college degree by age 26, compared with 51 percent of students from families in the highest socioeconomic quartile (Haveman & Smeeding, 2006).…”
Section: Introductionmentioning
confidence: 98%
“…Gaps in college degree attainment by socioeconomic status are even more pronounced. Among the high school graduating class of 1992, only 7 percent of students from families in the lowest socioeconomic quartile completed a four-year college degree by age 26, compared with 51 percent of students from families in the highest socioeconomic quartile (Haveman & Smeeding, 2006).…”
Section: Introductionmentioning
confidence: 98%
“…[9] Other studies have explored claims of university as a means for social mobility. [25,41,60] In the UK, the discussion about the effect of university is often framed in terms of "graduateness". According to Glover et al, graduateness can be "defined as the effect on knowledge, skills and attitudes, of having undertaken an undergraduate degree…."…”
Section: Introduction and Graduatenessmentioning
confidence: 99%
“…Concurrently, over the parallel period from 2001-2010, Knapp, Kelly-Reid, and Ginder (2010) detailed that the price of college attendance over that time rose anywhere from 30% to 47% dependent on the type of institution. While cost is one factor under investigation by current literature, other studies (Bastedo & Jaquette, 2011;Davis 2003;Haveman & Smeeding 2006;Page & Scott-Clayton, 2016) have suggested that institutional practice may have also played a direct role in these enrollment trends. Even after low SES students have overcome the hurdle of enrolling in college, they are met with the challenge of remaining enrolled through to completion and have higher rates of attrition than do their peers (Chen & DesJardins, 2008).…”
Section: Statement Of the Problemmentioning
confidence: 99%
“…Hearn's research was extended directly by Karen (2002) who found specifically that low socioeconomic background, when controlling for all academic factors, directly affected post-secondary destination. Beyond Karen (2002), many studies (Bastedo & Jaquette, 2011;Dougherty & Kienzl, 2006;Haveman & Smeeding, 2006;Lovenheim & Reynolds, 2011) went on to use the NELS data as well as other nationally representative data sets. Almost all found an increasing, or, at the very least, a steady rate of stratification across socioeconomic background by institutional type in the United States.…”
Section: Barriers To Low Ses Student Enrollmentmentioning
confidence: 99%
See 1 more Smart Citation